Effects of Ferrous Nanoparticles of Psidium guajava (Linn.) Leaf on Liver Functions in Male Wistar Rats - Mustapha, Musa Azegya; A., Arowora K.; S, Ezeonu C.; Umaru, Isaac John (African Journal of Biochemistry and Molecular Biology Research, 2025)
This study evaluated the effects of ferrous nanoparticles (FeNPs) derived from Psidium guajava L. leaves on liver function in male Wistar rats. Fresh leaves were harvested from the Government Reservation Area (G.R.A), Wukari, Taraba State, washed, air-dried, and pulverized prior to FeNP preparation. Twenty-five male albino rats (140–190 g) were randomly assigned to five groups, with Group 1 serving as the control and Groups 2–5 receiving oral FeNP doses of 100, 250, 500, and 1000 ppm, respectively, for three weeks. Post-treatment, serum samples were collected under chloroform anaesthesia for biochemical and histological analyses. Liver function tests revealed non-significant differences (p > 0.05) in measured parameters between Groups 1 and 3, whereas Groups 2, 4, and 5 showed significant alterations (p < 0.05) compared with the control. Aspartate aminotransferase (AST) levels increased significantly in Groups 3–5, while Group 2 showed no significant change; alanine aminotransferase (ALT) levels increased significantly in all treated groups except Groups 3 and 4. Albumin concentrations were significantly elevated across all treated groups. Total bilirubin (TB) and indirect bilirubin (IDB) remained unchanged in Group 2 but increased significantly in Groups 3–5, whereas direct bilirubin (DB) did not differ in Groups 2 and 3 but rose significantly in Groups 4 and 5. Total protein (TP) levels were comparable between Groups 1 and 2 but were significantly higher in Groups 3–5. Malondialdehyde (MDA) levels did not differ significantly among groups, although apparent increases were observed, while catalase (CAT) activity was significantly elevated in all treated groups, peaking in Group 5. Superoxide dismutase (SOD) activity remained unchanged in Groups 2 and 3 but increased significantly in Groups 4 and 5. Histological examination revealed dose-dependent structural abnormalities in liver tissue, with the most pronounced damage observed in Group 5. Overall, FeNPs from Psidium guajava leaves induced dose-dependent alterations in liver function and antioxidant enzyme activity in male Wistar rats, with higher doses, particularly 1000 ppm, associated with marked biochemical disturbances and histological damage, suggesting potential hepatotoxicity at elevated concentrations and underscoring the need for further studies to define safe exposure thresholds and long-term effects.